(untitled) (Window of Public Health Journal, 2026)
Antenatal Care (ANC) is a form of health service provided to pregnant women before giving birth, with the aim of building trust, detecting potential complications, preparing for childbirth, and providing health education. This study aims to determine the relationship between Antenatal Care (ANC) and the incidence of stunting at the Sumbang Community Health Center, Enrekang Regency. This study uses a quantitative research method with a cross-sectional approach. The sampling method in this study uses a random sampling technique with sampling using the Slovin formula, so that the number of samples in this study is 175 mothers who have toddlers aged 0-60 months in the working area of ​​the Sumbang Community Health Center, Enrekang Regency. The data analysis used is univariate analysis and bivariate analysis. According to the results of the bivariate analysis using the chi-square test, it shows that two variables, namely the Frequency of Antenatal Care Visits (p = 0.000 <0.05) and Antenatal Care Service Standards, which include adherence to recommended checkup schedules, nutritional counseling, and risk factor screening (p = 0.002 <0.05), are significantly related to the incidence of stunting. This study concluded that there is a relationship between the frequency of antenatal care visits and the standard of antenatal care services with the incidence of stunting, while the quality of antenatal care is not related to the incidence of stunting. Community health centers are advised to further optimize antenatal care (ANC) services, particularly in terms of educating pregnant women about the importance of regular and comprehensive prenatal checkups, including nutritional support, early detection of risk factors, and stunting prevention during pregnancy. Pregnant women are also advised to be more aware of the importance of conducting regular ANC visits in accordance with established standards. The community is also expected to be more proactive in supporting the health of pregnant women and children as an effort to prevent stunting.